PENGEMBANGAN KOMPETENSI TEKNOLOGI INFORMASI KOMUNIKASI BAGI APARATUR SIPIL NEGARA DINAS KOMUNIKASI, INFORMATIKA, DAN STATISTIK KABUPATEN BANDUNG (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2022)
The development of Information and ommunication Technology (IT) competencies is an important thing that the Civil Servant (ASN) needs to be able to carry out their duties in the digital era. One of the implementations of digitalization in government organizations is e-government. One of the regional apparatus that is close toimplementing e-government is the Department of Communication, Informatics and Statistic, Bandung Regency. As a leading sector in the field of technology in Bandung Regency, it is necessary for ASN who have competence in the field of ICT. But in fact, the number of employees who have competence in the field of ICT is still minimal so that it makes the authors interested in conducting this research. The purpose of this study was to determine the implementation of ICT competency development for ASN at the Department of Communication, Informatics and Statistic, Bandung Regency throught Hasibuan’s (2007) theory study which consist of 2 dimensions, namely formal development and informal development. This study use a qualitative descriptive method with an inductive approach. Based on the results of the research, it is known that the implementation of formal competency development is carried out throught education and training in collaboration with third parties and requires a budget so that it cannot be implementation evenly. Meanwhile, informal competency development is carried out by means of independent training so that it cannot obtain maximum results compared to throught education and training. Efforts are being made to improve the competence of ASN in the ICT sector by prioritizing the training budget, as well as motivating unskilled employees to improve their competence by learning from more skilled colleagues so as to create a work team that can work together to support organizational performance. Keywords : Competency Development, Information and Communication Technology, Civil Servant